2020
DOI: 10.1093/milmed/usaa004
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Mechanisms of Musculoskeletal Injuries in Deployed Navy Active Duty Service Members Aboard Two U.S. Navy Air Craft Carriers

Abstract: Introduction This brief report describes the number and nature of cases of musculoskeletal pain and injury among sailors and marines presenting to the ship’s physical therapist during recent, respective deployments of two U.S. Navy aircraft carriers. Materials and Methods The case definition for this study was cases of work-limiting medical complaints involving the musculoskeletal system presenting, or referred, to the ship’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…The ergonomic intervention in this study had the effect of reducing the workers' musculoskeletal complaints with regard to their backs, waists, left and right thighs, right knees, right ankles, and left legs. Meanwhile, the effects of the work organization improvements in similar studies also showed a reduction in complaints of pain in the neck, shoulders, hands, lower back, and legs [44]; lower back, shoulders, and knees [45]. However, complaints in the neck and upper back had the highest prevalence rates, amounting to 55.8% and 89.9%, respectively [46].…”
Section: Body Areamentioning
confidence: 84%
“…The ergonomic intervention in this study had the effect of reducing the workers' musculoskeletal complaints with regard to their backs, waists, left and right thighs, right knees, right ankles, and left legs. Meanwhile, the effects of the work organization improvements in similar studies also showed a reduction in complaints of pain in the neck, shoulders, hands, lower back, and legs [44]; lower back, shoulders, and knees [45]. However, complaints in the neck and upper back had the highest prevalence rates, amounting to 55.8% and 89.9%, respectively [46].…”
Section: Body Areamentioning
confidence: 84%
“…A total of 17 studies (published between 2000 and 2021, the epidemiology data were collected between 1980 and 2016) were included in this systematic review. In terms of the study design, 1 study [20] was a prospective study, 9 studies [21][22][23][24][25][26][27][28][29] used a retrospective study design, and 7 studies [13,[30][31][32][33][34][35] were crosssectional studies. Fifteen articles originated from the United States, and the 2 other studies [13,34] originated from China and Brazil.…”
Section: Descriptive Characteristics Of the Studiesmentioning
confidence: 99%
“…Fifteen articles originated from the United States, and the 2 other studies [13,34] originated from China and Brazil. Of those, 9 articles [13,20,21,28,[30][31][32][33][34] reported the sample size ranging from 210 to 424596, and 5 studies [13,30,[32][33][34] reported participants' age; the mean age ranged from 19.32 to 28.80 years. Five studies [13,20,21,28,30] involved both female and male participants, with the percentage of females varying between 11.77% and 39.73%, but 3 studies [32][33][34] recruited only male subjects.…”
Section: Descriptive Characteristics Of the Studiesmentioning
confidence: 99%
See 2 more Smart Citations